Application of heuristics for packing problems to optimise throughput time in fixed position assembly islands. (18th July 2022) - Henke, Thomas; Deuse, Jochen
Accompanied with globalisation, companies are confronted with new competitors and price competitions. In order to meet these challenges manufactures strive to increase their efficiency throughout the value stream. Especially special machine manufactures assembling in fixed position assembly islands show a high non-value adding share, since their assembly and logistical processes are characterised by a low degree of standardisation and maturity. This leads to a high spread of throughput times and increases the risk of delivery delays. To improve this weakness, this paper presents an approach to increase the degree of standardisation and to lower and stabilise the throughput time. The new approach bases on heuristics for packing problems and applies them to the material supply. By that, the allocation of the supplied components is optimised, as a result of which search times and path lengths for walking and transporting are shortened and the value adding time share is increased.